2018
DOI: 10.1002/adma.201803924
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Visualization of Stress/Strain Distribution and Fatigue Crack Propagation by an Organic Mechanoresponsive AIE Luminogen

Abstract: Stress exists ubiquitously and is critically important for the manufacturing industry. Due to the ultrasensitive mechanoresponse of the emission of 1,1,2,2,-tetrakis(4-nitrophenyl)ethane (TPE-4N), a luminogen with aggregation-induced emission characteristics, the visualization of stress/strain distributions on metal specimens with a pure organic fluorescent material is achieved. Such a fluorescence mapping method enjoys the merits of simple setup, real-time, full-field, on-site, and direct visualization. Surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 38 publications
1
91
0
Order By: Relevance
“…In recenty ears, the great development of AIE compounds is relatedtomultiple potential applications, including luminescent probes for biomedical imaging and sensing applications, which are under intensive development. [9][10][11][12][13][14][15][16][17][18] Because of their twisted conformations, AIE-active organic molecules usually aggregate into al oosely( defective) packed solid state that facilitates their transformation between differ-ent molecular arrangements. This characteristicc onfers an enhanced sensitivity to externals timuli and, in particular, to mechanical forces onto thesec ompounds.…”
Section: Introductionmentioning
confidence: 99%
“…In recenty ears, the great development of AIE compounds is relatedtomultiple potential applications, including luminescent probes for biomedical imaging and sensing applications, which are under intensive development. [9][10][11][12][13][14][15][16][17][18] Because of their twisted conformations, AIE-active organic molecules usually aggregate into al oosely( defective) packed solid state that facilitates their transformation between differ-ent molecular arrangements. This characteristicc onfers an enhanced sensitivity to externals timuli and, in particular, to mechanical forces onto thesec ompounds.…”
Section: Introductionmentioning
confidence: 99%
“…(E) Working mechanism for stress/strain visualization. [76] have been realized and well investigated. The unique fluorescent behaviors provide severala dvantages for visualization in materials science.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, Tang, and co-workers have found that the tetrakis(4-nitrophenyl)ethane( TPE-4N) exhibited as ensitivef luorescent response towards mechanical stimulus. [76] The TPE-4N molecules showedn oe mission in their crystalline form, and strong fluorescent emission can be observedf or their amorphous fragments upon mechanical force. Notably,t he fluorescence intensity ratio in amorphous and crystalline states is up to 23, suggesting the high contrast and sensitivity of the molecules in different states.…”
Section: Mechanical Responsesmentioning
confidence: 98%
See 2 more Smart Citations